Image of Lithuanian Communists who Broke away from Moscow in the TV Show “Panorama” of the Lithuanian Television in January-March 1990 - Aluzas, Lukas (Žurnalistikos tyrimai, 2021)
The transformation of communist societies into democratic ones in Europe in 1988-1990 is a massive and complicated phenomenon. Claiming that they were implementing democracy, the local communist regimes had been trying to maintain their influence in the states, for which they had a lot of resources, including the media. In terms of political communication, the mass media claimed not even the position of an individual actor next to politicians or the audience, but a puppet group of politicians. The liberating society began to look at non-communist political alternatives, while the communists were trying to maintain a monopoly. This also happened in 1990 in Lithuania, which was occupied by the Soviet Union. Hence the question arises, as the first democratic elections after the Second World War had approached, how did the media describe the Lithuanian Communist Party that seized power? Consecutive newspaper archives have survived to this day, therefore we can clearly see how the press has reflected the news of the political field. But what and how was streaming media TV broadcasting? Often these were working at the time say “I don’t remember anything” or tell generalized narratives. In addition, there is an argument that there are little remains left of the programs, which cannot provide a full context of what and how television had been showing. Based on the thesis of television theory and practice that a television report or other production is created based on a text, the texts of the program “Panorama” stored in the Central State Archive of Lithuania are used to prepare the article. The purpose of this article is to show how the journalists reflected the events related to the Lithuanian Communist Party in the main informational television show, what attitudes of the audience could be formed on this political force during the election campaign. The article publishes an analysis of the texts of the TV show “Panorama” related to the Lithuanian Communist Party, its leader Algirdas Brazauskas and the party’s activities.